The Effect of Plant Characteristics on CO2 Emission Factor Development: A Case Study of Coal-Fired Power Plants in Indonesia - Prakarsa, Widya Utama; Dewi, Kania (Journal of Community Based Environmental Engineering and Management, 2024)
The emission factor (EF) describes the relationship between pollutants released into the atmosphere and associated activities. Developing specific EFs is essential for accurate emission calculations in the industrial sector, particularly in coal-fired power plants (CFPPs), a major source of emissions in Indonesia. This study aims to develop specific CO2 EFs for CFPPs in Indonesia by analyzing the influence of power plant characteristics, such as technology type and age, on the EF values. The EFs, expressed in tons of CO2 per unit of energy produced (t TJ-¹), are based on data from 153 units across 66 CFPPs in Indonesia. Five technology types were included in the analysis: ultra-supercritical, super-critical, subcritical-pulverized coal combustion, subcritical-fluidized bed combustion and subcritical–stoker. The study compares the resulting CO2 EFs with the IPCC-2006 default value for sub-bituminous coal and Indonesia’s national EF for medium-quality coal. The average CO2 EF for Indonesian CFPPs was 100.16 t TJ-1, higher than the IPCC-2006 default value (96.1 t TJ-1) but slightly lower than Indonesia’s national EF (100.575 t TJ-¹). A statistical test revealed significant differences between technology and age groups, but post-hoc analysis showed no strong correlation was found between these characteristics and the EF values within specific groups. This indicates that the EF, based on fuel characteristics, is not directly influenced by these plant characteristics. It is hoped that the CO2 EF values obtained from this study will better represent actual conditions, provide a more accurate emission calculations and supporting the development of better emission inventories for cleaner energy generation.